Nilai-Nilai Profetik dalam Pendidikan Karakter sebagai Bahan Ajar Sastra di SMP: - Herawati, Tri Ratna; Tyas Palupi, Muncar (Jurnal Korpus, 2025)
The focus of this research is prophetic values in folklore in the form of examples of changes in behavior, attitudes, science, both habluminalloh and habluminannas in order to create a harmonious balance in students. This research uses qualitative description methods using documentation techniques. Data source in the form of Indonesian folklore books on the island of Java. Of the several Indonesian folk tales selected, there are 5 (five), namely the folk tales (1) Nawangwulan, (2) Bawang Merah Bawang Putih, (3) Cindelaras, (4) Sangkuriang, and (5) Roro Mendut. The five folk tales are analyzed using steps to read, observe, record, identify and analyze from the aspects of humanization, liberation and transcendence in the five contents of the folk tale. Content and meaning analysis is used which is carried out objectively and transparently and arranged systematically and comprehensively to draw research conclusions. The results of this research show that there are prophetic values found in the five Indonesian folk tales. The meaning contained in the five Indonesian folklore is related to (1) humanist (humanity), namely instilling a soul based on the principle of humanity; and the interests of fellow human beings and being devoted to parents, (2) liberation, namely the soul upholding honesty and justice, and (3) transcendent, namely instilling devotion with gratitude and istiqomah in getting closer to God Almighty. Choosing the right folklore will be beneficial in character education for students in Junior High School.